QORAQALPOGʻISTON BURILISh YILIDA (1989) - Kochanov, B.A.; Yusupov, K.A. (SCIENCE and SOCIETY, 2023)
The article highlights the history of Karakalpakstan at a turning point: when national cadres came to power after the tragic events of the “cotton business”. Based on the latest literature and archival sources, the authors restore these dramatic pages of our people.
Keywords: Uzbekistan; Karakalpakstan; "Cotton business"; I. Karimov; S. Niyetullaev; history; repressions; economy; social status